2011
DOI: 10.1094/cchem-08-10-0111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wheat Genotype and Environment on Relationships Between Dough Extensibility and Breadmaking Quality

Abstract: Cereal Chem. 88(2):201-208Dough extensibility affects processing ease, gas retention, and loaf volume of finished products. The Kieffer dough extensibility test was developed to assess extensibility of small dough samples and is therefore adapted for use in breeding programs. Information is lacking on relationships between wheat growing environments and dough properties measured by the Kieffer dough extensibility test. This study documents the variability of dough extensibility (Ext), maximum resistance to ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 22 publications
2
32
1
Order By: Relevance
“…The highest correlation coefficient with pan loaf volume was observed with Alveograph L or "extensibility". The importance of extensibility was previously reported with South American wheats (Vázquez & Watts, 2004) and also with an independent set of samples (Caffe-Treml et al, 2011). No Mixolab parameter had significant correlation with pan loaf volume.…”
Section: Ijfs April 2015 Volume 4 Pages 78-87supporting
confidence: 58%
See 1 more Smart Citation
“…The highest correlation coefficient with pan loaf volume was observed with Alveograph L or "extensibility". The importance of extensibility was previously reported with South American wheats (Vázquez & Watts, 2004) and also with an independent set of samples (Caffe-Treml et al, 2011). No Mixolab parameter had significant correlation with pan loaf volume.…”
Section: Ijfs April 2015 Volume 4 Pages 78-87supporting
confidence: 58%
“…Lack of consistency among different results could be explained by the small number of samples used; more likely, it could be explained by the different characteristics of the wheats under study. These differences were also observed in research involving other rheological properties (Caffe-Treml et al, 2011). Therefore, in order to establish the suitability of a new method, it is essential to evaluate it with a set of samples representative of the population that will use it.…”
Section: Ijfs April 2015 Volume 4 Pages 78-87mentioning
confidence: 99%
“…The dough extensibility values (36.5-44.4 mm) of flour prepared from the HRS (CWRS, NS, and DNS) were higher than those of the SW10.5 (16.4 mm) or ASW (19.7 mm). Nash et al (2006) and Caffe-Treml et al (2011) reported that increased dough extensibility enhanced bread rising to form a larger loft volume. The results in this study showed higher dough extensibility and lower resistance for flour from the hard wheat than the soft wheat type, with correspondingly higher expected bread volumes (Table 3).…”
Section: Dough and Bread Propertiesmentioning
confidence: 99%
“…The ability of such sprout-tolerant genotypes to overcome this adverse environmental factor might be expressed as 'G x e'. Dough strength appears to be affected by equal contributions from genotype and growth conditions for dough quality (Wrigley & Batey, 2003, Caffe-Treml et al, 2011, indicated above as a potential source of 'nasty surprises' for millers and bakers. It is well accepted that many aspects of growth environment affect dough quality (Gooding, 2010, Caffe-Treml et al, 2011.…”
Section: Introductionmentioning
confidence: 98%
“…Dough strength appears to be affected by equal contributions from genotype and growth conditions for dough quality (Wrigley & Batey, 2003, Caffe-Treml et al, 2011, indicated above as a potential source of 'nasty surprises' for millers and bakers. It is well accepted that many aspects of growth environment affect dough quality (Gooding, 2010, Caffe-Treml et al, 2011. Heat stress (a few days of >35 o C) during grain filling has been reported to cause dough weakness in the resulting grain (Corbellini, 1998;Blumenthal, 1995).…”
Section: Introductionmentioning
confidence: 98%